Learning to Feel? An Essay on Death, Sex and Tricksterism in Todd Phillips’s Joker (2019) - Kanerva Kirsi (Finland, 2022)
In this essay, I will discuss some of the opportunities offered by Todd Phillips’s Joker (2019) to engage in an “interpretative play,” to use the term of Noël Carroll, with this particular work of art, and consider some of the emotional responses that the movie elicits. The perspective in this free-associative essay is subjective, and the aesthetic and non-aesthetic responses to the film elaborated here concentrate on the following selected themes: emotions and sexuality as part of the Joker’s origin story and the Joker’s role as an archetypal trickster in the Jungian sense.